Age and Sex Differences in Hearts of Soluble Epoxide Hydrolase Null Mice - Jamieson, K. Lockhart; Keshavarz-Bahaghighat, Hedieh; Darwesh, Ahmed M.; Sosnowski, Deanna K.; Seubert, John M. (Frontiers in Physiology, 2020)
Biological aging is an inevitable part of life that has intrigued individuals for millennia. The progressive decline in biological systems impacts cardiac function and increases vulnerability to stress contributing to morbidity and mortality in aged individuals. Yet, our understanding of the molecular, biochemical and physiological mechanisms of aging as well as sex differences is limited. There is growing evidence indicating CYP450 epoxygenase-mediated metabolites of n-3 and n-6 polyunsaturated fatty acids are active lipid mediators regulating cardiac homeostasis. These epoxy metabolites are rapidly hydrolyzed and inactivated by the soluble epoxide hydrolase (sEH). The current study characterized cardiac function in young and aged sEH null mice compared to the corresponding wild-type (WT) mice. All aged mice had significantly increased cardiac hypertrophy, except in aged female sEH null mice. Cardiac function as assessed by echocardiography demonstrated a marked decline in aged WT mice, notably significant decreases in ejection fraction and fractional shortening in both sexes. Interestingly, aged female sEH null mice had preserved systolic function, while aged male sEH null mice had preserved diastolic function compared to age WT mice. Assessment of cardiac mitochondria demonstrated an increased expression of acetyl Mn-SOD levels that correlated with decreased Sirt-3 activity in aged WT males and females. Conversely, aged sEH null mice had preserved Sirt-3 activity and better mitochondrial ultrastructure compared to WT mice. Consistent with these changes, the activity level of SOD significantly decreased in WT animals but was preserved in aged sEH null animals. Markers of oxidative stress demonstrated age-related increase in protein carbonyl levels in WT and sEH null male mice. Together, these data highlight novel cardiac phenotypes from soluble epoxide hydrolase null mice demonstrating a sexual dimorphic pattern of aging in the heart.